Fundamental and behavioural factors determining bank officers’ credit decision for SME lending in Malaysia / Nigel Kollin Ondolos - Ondolos, Nigel Kollin (2022)
In Malaysia commercial banking practice, credit analysis for SMEs loan application involved an internal credit officers’ quantitative and qualitative decision making process. Based on the bounded rational theory, ideally, bank credit officers would be influenced by both fundamental factors and behavioural factors in their credit assessment and decision making process. While the fundamental factors are widely acknowledged, the behavioural factors are under-researched. This research aims to study the fundamental and behavioural factors determining bank officer credit decision for SMEs lending in Malaysia using the theoretical lenses of behavioural finance. Analyses are conducted using hierarchical multiple regression as a main analysis. In addition, multiple linear regression and mean centered approach are performed as robustness analysis. In finding ways to reduce behavioural biases, the moderating role of human capital factor on the relationship between behavioural factors on behavioural credit decision are examined. The data for the study were obtained from survey involving 161 bank credit officers in development financial institutions and commercial bank. The selected sampling technique adopted for this study is non-probability combining quota and purposive sampling technique. Hierarchical multiple regressions was used to examine the relationship between the fundamental factors, behavioural factors and human capital factors on bank officers’ credit decision for SMEs lending. The analyses also been control by gender and age. On the fundamental factors assessment, regression results showed that character and condition are positively significant related to the fundamental credit decision making. On the behavioral factors assessment, intuition, overconfidence and loss aversion are positively significant related to the behavioural credit decision making. On the interaction analysis, the findings indicate that; (i) credit experience is negatively significant in moderating intuition and overconfidence influence on behavioural credit decisions; (ii) emotional intelligence is negatively significant in moderating intuition, loss aversion, optimism, and overconfidence influence on behavioural credit decisions. Overall, the findings of this study would be valuable in enhancing the SMEs lending theory, policy and practice.